Palaeoenvironments Of The Permian-Cretaceous Sediments Of The Bintuni Bay, Papua - Eko B Lelono; Mufdi Firdaus; Tri Bambang SR (Testing Center for Oil and Gas LEMIGAS, 2010)
This paper presents a part of the result of Lemigas in-house research entitled Paleogeography and Hydrocarbon Potentiality of the pre-Tertiary Sediment of the Bintuni Basin, Papua, which is financially supported by the Government through a project so called DIPA 2009. In addition, this paper specifically discusses a palaeoenvironment of the Late Permian-Cretaceous sediment of the Bintuni Bay based on biostratigraphy. Data used in this paper is mostly secondary data obtained from National Data Center and an oil company which is therefore, classified as a confidential information. Paleoenvironment appeared in a non-marine setting during Permian-Triassic to form Ainim Formation in which, shale of this formation acts as a primary sourcerock for the studied area. Early Jurassic is characterised by a non-deposition, whilst Middle Jurassic is indicated by the occurrence of non-marine environment to deposit fluvial sandstone of the Lower Kembelangan Formation which is considered to be a main reservoir. Subsequently, environment shifted to the marine setting where deep marine shale occurred to form caprock. Mean while, the Early Cretaceous sediment disappears from the studied area suggesting massive erosion. Finally, depositional environment took place in the marine setting during the Late Cretaceous resulting in the formation of deep marine shale of Jass Formation which may contribute as a caprock in the element of petroleum system